COMMON SELF-EVALUATION FRAMEWORK (CAF) FOR THE EDUCATION SYSTEM - Alexandra IANCU (Challenges of the Knowledge Society)
Public administrations are faced with a variety of challenges, contexts and circumstances, including social problems and social exclusion caused by financial and economic crises, low levels of trust in politicians and public institutions, demographic changes, the rapid development of information and communication technologies and the development of a differentiated civil society with new information and communication needs, which require inclusion in active policy formulation and decision-making. All Member States have established cooperation between different levels of government and institutions dealing with the quality of universities, public administration institutes and private organisations. Despite all the common features of an established organisational structure for promoting quality, there are significant differences between the actual organisational units of the counties and the way they cooperate with other actors in the field of quality management.